Pengaruh Kecerdasan Emosonal, Kecerdasan Spiritual dan Perilaku Belajar Terhadap Tingkat Pemahaman Akuntansi - Mauliza Putri Azzahra; Yayuk Nurjanah (Forum Dosen Indonesia, 2022)
To produce qualified accounting graduates, universities must know what factors influence a student in understanding the material he gets, generally the education system is only centered on intellectual intelligence, it should also be balanced with other intelligences such as emotional and spiritual intelligence. This intelligence is personality intelligence such as how to develop heart intelligence with toughness, initiative, honesty, and adaptability. Some examples in our environment that prove that having brain intelligence alone, or many who have high degrees does not determine success in taking part in the world of work. The purpose of this study was to determine the effect of emotional intelligence, spiritual intelligence, and learning behavior on accounting understanding in accounting study program students. This type of research is quantitative research. The research subjects used by the authors are Accounting Study Program students in Bogor with a population of 4,468 people consisting of 3,475 Bachelors in Accounting and 993 D3 Accounting students. The data collection in this study used primary data with research instruments using a questionnaire via Google Form which was distributed directly to the research sample through social media as measured by a Likert scale. The sample selection technique used purposive sampling with sampling based on criteria that had been determined by the author with the sampling unit through the Slovin formula totaling 368. The data analysis technique was carried out using Multiple Linear Regression Analysis with the help of SPSS (Statistical Product and Service Solutions) Version 16. The results showed that partially (1) emotional intelligence had a significant positive effect on accounting understanding, (2) spiritual intelligence had a significant effect on accounting understanding, (3) learning behavior had a significant effect on accounting understanding, and (4) simultaneously showed that the variable emotional intelligence, spiritual intelligence, and learning behavior affect the understanding of accounting. Keywords: Emotional Intelligence, Spiritual Intelligence and Learning Behavior.